"That shit doesn't fly": subcultural constraints on prison radicalization - Bucerius, Sandra M. (Criminology, 2023)
Many observers describe prison subcultures as inherently and irredeemably antisocial. Research directly ties prison subcultures to violence, gang membership, and poor reintegration. In extreme cases, research has also suggested that prison subcultures contribute to incarcerated people joining radical groups or embracing violent extremist beliefs. These claims, however, ignore key differences in the larger cultural and social context of prisons. We examine the relationship between prison subcultures and prison radicalization based on semistructured qualitative interviews with 148 incarcerated men and 131 correctional officers from four western Canadian prisons. We outline several imported features of the prison subculture that make incarcerated people resilient to radicalized and extremist messaging. These features include 1) national cultural imaginaries; 2) the racial profile of a prison, including racial sorting or a lack thereof; and 3) how radicalization allowed incarcerated men and correctional officers to act outside the otherwise agreed-to subcultural rules. Our research findings stress the importance of contemplating broader sociocultural influences when trying to understand the relationship between radicalization and prison dynamics and politics.